The Effect of Employee Training and Development on Employee Performance of the Department of Education, Youth and Sports in Labuan Bajo, West Manggarai - Andi Arifuddin Iskandar; Oktavianus Tedim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of employee training and development on the performance of the youth education and sports department of Labuan Bajo, West Manggarai. The population in this study were 43 respondents. Data collection techniques in this study are the distribution of questionnaires and questionnaires. The data analysis used in this study were: validity test, reliability test, normality test, multicollinearity test, Heteroskedasticity Scatter Plot test, multiple regression analysis, coefficient of determination test, t test (partial test), hypothesis test 1 (the effect of training on performance) , test hypothesis 2 (influence of development on performance), F test (simultaneous test). The results of this study can be concluded that: Partially training has a positive and significant effect on the performance of the Department of Education and Sports of Labuan Bajo Manggarai Barat, Partially development has a positive and significant effect on the performance of the Department of Education and Sports of Labuan Bajo Manggarai Barat, Simultaneously training and development has a positive and significant effect on the performance of the West Labuan Bajo Manggarai Education and Sports Office employees and the most dominant variable that affects the performance of the West Labuan Bajo Manggarai Education and Sports Office employees is the development variable.